Cornual molar ectopic pregnancy - Cakmak, Bulent; Toprak, Muhammet; Nacar, Mehmet Can; Koseoglu, Resid Dogan; Demirturk, Fazli (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
The aim of this study is to present a rarely seen cornual molar ectopic pregnancy case regarding with literature. 36 years old patient with the third pregnancy was referred to our clinic with the prediagnosis of viable ectopic pregnancy. The patient had two vaginal delivery history and she had vaginal bleeding as spotting onwards fifteen days. Ultrasonographicassessment demonstrated ectopic pregnancy with positive fetal cardiac activity and 8mm crown-rump length (6W5D) at right cornual region. The patient was performed cornotomy with laparotomy. Postoperative pathological evaluation was reported as a partial molar pregnancy. β-human chorionic gonadotropin (β-hCG) values declined dramatically and so additional treatment was not applied. Molar ectopic pregnancy findings are usually seen as conventional pregnancies and β-hCG values and histopathological evaluation is important for correct diagnosis and follow up.